Plot and Composition of the Epos - Manzura Narzikulova (Researchparks Publishing, 2022)
The article describes the plot and composition of the epic - poetically perceived main and auxiliary ideas through a combination of motives, as well as some comments on their expression in a certain form. An artistic idea is being explored - the idea of the family of the epic